Manajemen Pengadilan Agama dalam Memediasi Perceraian di Kota Medan - Nasution, Dahliana; Walisyah, Tengku (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The high divorce rate in Medan City identifies special factors that contribute to the dynamics of divorce in this region involving economic, cultural and social aspects. This research aims to find out the management of the Religious Courts in carrying out divorce mediation in Medan City, find out the mechanism of divorce mediation in the Medan Religious Courts and find out the obstacles in carrying out divorce mediation. The method used in this research is a qualitative descriptive method, an approach through observation, interviews and documentation studies. This research uses observation techniques on mediators in mediating divorce at the Religious Court on Jalan Sisingamaraja, Medan Amplas District. Interviews were conducted by researchers with the chief judge and reporting section staff, and data documentation studies were obtained from several references and literature related to the research. From the research results, it is known that the management of the Religious Courts in divorce mediation in Medan City is carried out professionally and neutrally, the work system is mutually sustainable in carrying out mediation and has a functional relationship so that the mediator used is effective. The Religious Court mechanism for conducting divorce mediation has several stages, where the first stage is called pramediası, the second stage is called mediation, and the third stage is called caucus. The Medan City Religious Court has implemented a method to make mediation more effective, namely the method used is called a caucus, often also called a separate meeting between the mediator and one of the interested parties so that it can be open and the mediator can understand the existing problems and find solutions and mediation can be successful quickly. The obstacle found in the Religious Courts in carrying out divorce mediation in Medan City is inadequate facilities which cause discomfort for both parties. Economic factors can also be an obstacle to lack of funds, another obstacle is the lack of optimality of judges in acting as mediators.